Association of Low Ferritin Level of new Born with Iron Deficiency Anemia in Mothers - Saiqa Zahoor, Aqsa Latif, Hammad Khan, Maida Khalid, Syeda Zainab Kanwal Bukhari, Shazia Ambreen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Iron deficiency and iron-deficiency anemia (IDA) affect around 2 billion individuals all over the globe. IDA is a problem for pregnant women in developing countries. Objective: To assess the association of low ferritin level of new born with iron Deficiency Anemia in Mothers Methodology: The current descriptive study was carried out at the Hematology Department, Hayatabad Medical Complex, Peshawar from January 2022 to July 2022. All the data including age, gender and lab parameters was documented in a proforma designed for this research. IBM SPSS version 23 was employed for analysis of data. Results: In the current research, totally 150 antenatal mothers having hemoglobin ≤10.5gm/dl were enrolled. The mean age of our study participants was 26 years with standard deviation of ±1.56. Among pregnant women with iron deficiency, the overall frequency of low ferritin level was 90 (60%). In distribution of women based on severity of low ferritin levels amongst 90 women, 41 (45.56%) women were observed with mild low ferritin levels, 43 (47.78%) women were observed with moderate low ferritin levels while 6 (6.66%) women were observed with severe low ferritin levels. Conclusion: In the present research, it was shown that there was a high frequency of low ferritin levels in newborns amongst women with iron deficiency anemia during pregnancy. Based on our findings we concludes that low ferritin level of newborns is strongly associated with the with iron Deficiency Anemia in Mothers. Keywords: Iron Deficiency Anemia; Ferritin levels; Pregnancy